Prioritization of Development Strategies Based on the Existing Business Model Canvas at Beras Basah Island - Nur Indah Sari; Heru Susilo; Erwiantono; Fitriyana; Juliani (Universitas Islam Lamongan, 2025)
This study aims to determine the mapping of existing business strategies and to develop new business strategies into a business model canvas. The method used is descriptive qualitative. Data collection was carried out through observation, documentation and interviews. The collected data were analyzed using SWOT analysis and the results were described in nine elements of the Business Model Canvas. The results of the study indicate that the business strategy obtained from the mapping of the Business Model Canvas is quite good, because each element supports each other to increase income. Furthermore, several strategies need to be carried out to increase income and prioritize the concept of sustainable ecotourism such as publication and socialization of policies; determination of a management model based on the carrying capacity of the Area; integration between tourist destinations to create a tour package; collecting feedback to improve services; expanding market segmentation to foreign tourists; determining promotion costs, research and development; and optimizing opportunities through increasing MSMEs and the creative economy